Design model for composite beam‐to‐reinforced concrete wall joints. Issue 1 (6th February 2013) - Henriques, José; da Silva, Luís Simões; Valente, Isabel
Abstract A design model for composite beam‐to‐reinforced concrete wall joints is presented and discussed in this paper. The model proposed is the component method extended to this type of joint. The characterization of the active components is therefore performed in terms of force‐deformation curves. In this type of joint, special attention is paid to the steel‐concrete connection where "new" components, not covered in EN 1993‐1‐8, are activated. The application of the model allows the designer to obtain the joint properties in terms of the moment‐rotation curve. The accuracy of the proposed model is verified by comparing it with available experimental and numerical results. The latter were developed in the FE program ABAQUS and previously validated by experimental results.